Diskresi Penyelesaian Kasus Tindak Pidana Pelaku Pencabulan Dengan Kekerasan Terhadap Orang Dewasa - Fidelia Prabajati; Topo Santoso (Jurnal Interpretasi Hukum, 2024)
Criminal acts are often a topic in news media, social media and print media, as information about criminal acts or acts that sometimes disturb people's thinking, and the application of sanctions as regulated in the Criminal Code. Regarding case Number 100/Pid.Sus/2015/PN.Mrs, it is considered appropriate in the application of the article charged, but the fine is considered less effective because most perpetrators choose imprisonment instead of the fine. The author uses a normative qualitative method, with a case approach model based on the judge's decision in the court decision in case Number 833/Pid/B/2022/PN.JKT.Sel. with the result that imposing a sentence on the perpetrator of the crime of sexual immorality has sufficiently accommodated the perpetrator's behavior and is oriented towards justice for the victim because the sentence imposed by the judge is not too far from Article 82 paragraph (1) in conjunction with Article 76E of Law Number 35 of 2014 concerning Amendments to Law Number 23 2002 concerning Child Protection not only that, fines are imposed on perpetrators, although in practice many replace it with imprisonment, it is considered sufficient to be able to compensate for the losses suffered by victims of criminal acts of sexual abuse.